PENGARUH PENERAPAN TOTAL QUALITY MANAJEMEN TERHADAP KEPUASAN KERJA PEGAWAI DI UNIVERSITAS MUHAMMADIYAH BULUKUMBA - Jumase Basra (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2022)
This study aims to determine the application of TQM consisting of rewards and recognition, teamwork, organizational culture, education and training, organizational trust in employee job satisfaction. This research is a descriptive quantitative with a total research sample of 95 employees at the University of Muhammadiyah Bulukumba. The results of this study show that the variables of reward and recognition, teamwork, organizational culture, education and training, organizational trust have a significant effect on employee performance satisfaction. TQM affects simultaneously or together on employee job satisfaction.